2016
DOI: 10.1177/2324709616675645
|View full text |Cite
|
Sign up to set email alerts
|

Iron Overload and Platelet Function Defects

Abstract: Acquired platelet function defect might be a consequence of iron overload. Even though there are various complications of iron overload, only few reports have indicated some correlations with platelets dysfunction. We report a child with Diamond-Blackfan anemia who has significant complications from iron overload due to chronic blood transfusion, and one of these complications is acquired platelet function defect that manifests with frequent episodes of epistaxis. Therefore, we emphasize the necessity for furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
(20 reference statements)
1
5
0
Order By: Relevance
“…17,18,[26][27][28] There is some evidence that iron or ferritin has suppressive effects on hematopoietic cell proliferation and differentiation. [29][30][31] Furthermore, a possible correlation between iron overload and the defect in platelet function was explained by Dahi et al 32 In addition to direct impact, ferritin may have indirect effects on thrombocytopenia through pro-inflammatory roles. 33 Ferritin can trigger TIM-2 (immunoglobulin-domain and mucin-domain-2)-independent pathway (including PI3 kinase phosphorylation, protein kinase C zeta activation, and MAPK activation) that ultimately activates nuclear factor-kB (NF-kB).…”
Section: Discussionmentioning
confidence: 99%
“…17,18,[26][27][28] There is some evidence that iron or ferritin has suppressive effects on hematopoietic cell proliferation and differentiation. [29][30][31] Furthermore, a possible correlation between iron overload and the defect in platelet function was explained by Dahi et al 32 In addition to direct impact, ferritin may have indirect effects on thrombocytopenia through pro-inflammatory roles. 33 Ferritin can trigger TIM-2 (immunoglobulin-domain and mucin-domain-2)-independent pathway (including PI3 kinase phosphorylation, protein kinase C zeta activation, and MAPK activation) that ultimately activates nuclear factor-kB (NF-kB).…”
Section: Discussionmentioning
confidence: 99%
“…17 Although some studies revealed no agranulocytosis events 14,28 other reports have documented the correlation between acquired platelet defect and iron overload. 29 Nonetheless, no hemorrhagic episodes were reported among the patients in our study. Our results are in line with other studies which reported no significant impact of chelating agent on platelets count 14,30 but contradict other reports in which chelating agents caused thrombocytopenia.…”
Section: Discussionmentioning
confidence: 53%
“…We also found that haematoma volume mediated the association between an elevated haemoglobin level and poor outcomes in ICH. The pathophysiologic mechanism for this might be the result of multiple factors, such as the hemin-induced platelet-dependent thrombosis dysfunction or the iron toxicity and its related inflammation and coagulopathy 8 21–23. Although iron overload is not directly associated with high haemoglobin levels, however, iron dysregulation could be found in haematological disease such as polycythemia vera.…”
Section: Discussionmentioning
confidence: 99%